2012
DOI: 10.1149/2.006207jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Reference Electrode Position on the Measurement of Half Cell Polarization in Proton-Exchange Membrane Fuel Cells

Abstract: In this experimental and numerical study we analyze the polarization of the electrodes in a PEM fuel cell system. In order to measure the anode and cathode potential with respect to the electrolyte potential, a dynamic hydrogen electrode (DHE) is used as reference electrode. Two fundamental configurations for integrating a DHE into the membrane electrode assembly (MEA) are investigated: In the first configuration, the DHE is contacted to the membrane within a circular gap in the cathode catalyst layer, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Numerical calculations 4 have shown that the membrane potential at the RE is close to the potential of the working anode, i.e., 0. To explain this effect, calculations 4 were performed, assuming a very low in-plane proton conductivity of the membrane. Below, we will show that this effect arises, in fact, from the very large exchange current density of the anodic hydrogen oxidation reaction (HOR).…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…Numerical calculations 4 have shown that the membrane potential at the RE is close to the potential of the working anode, i.e., 0. To explain this effect, calculations 4 were performed, assuming a very low in-plane proton conductivity of the membrane. Below, we will show that this effect arises, in fact, from the very large exchange current density of the anodic hydrogen oxidation reaction (HOR).…”
mentioning
confidence: 91%
“…1a). This design is relatively easy to realize in polymer electrolyte fuel cells (PEMFCs) using a two-layer membrane with a platinum wire located between the layers 3,4 (Fig. 1a).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…An inappropriate perimeter-placed reference is sometimes used. 17,18 But most commonly, the ORR characteristics are simply assumed to dominate the signal to justify the use of a two-electrode setup, which appears reasonable given the higher exchange current density of the HOR. However, Kuhn et al 19 separated the contributions with a pseudo reference electrode sandwiched between the electrodes and found that the HOR impedance was not negligible under their conditions, but of the same order of magnitude across the entire cell impedance range.…”
Section: Introductionmentioning
confidence: 99%